Identification of C‐glycosyl flavones and quality assessment in Dendrobium nobile. (18th January 2021) - Wang, Yawen; Liao, Xian; Zhou, Chujuan; Hu, Li; Wei, Gang; Huang, Yuechun; Lei, Zhouxi; Ren, Zhiyao; Liu, Zhixia; Liu, Zhihua
Abstract : Rationale: Flavones are significant indicators of quality in traditional Chinese medicines (TCMs) and thus play a significant role in the quality control of TCMs in the pharmaceutical industry. Most flavones in Dendrobium nobile Lindl, a TCM with a long cultivation history and rich sources, have not been identified. This study was aimed at identifying the flavones in D. nobile from various habitats. Methods: High‐performance liquid chromatography (HPLC) coupled with diode‐array detection and HPLC multiple‐stage tandem mass spectrometry was used to identify the chemical constituents of D. nobile from various habitats, and a method was established to determine the content of vicenin II, violanthin and isoviolanthin. Hierarchical cluster analysis, principal component analysis and orthogonal partial least‐squares discriminant analysis were used to analyze the variations among 26 batches from different habitats. Results: A total of 33 flavones were tentatively identified. Twenty‐five flavones, previously undescribed in D. nobile, were acylated by p ‐coumaroyl, feruloyl, sinapoyl or 3‐hydroxy‐3‐methylglutaryl. The D. nobile habitats were distinguished by significant differences in their flavone content. The C‐glycosyl flavones were demonstrated to be characteristic compounds for evaluating D. nobile from various habitats. In particular, flavones acylated with 3‐hydroxy‐3‐methylglutaryl were specific compounds that were only detected in samples from Yunnan. Conclusions: The results of this study could be used to improve the quality control of D. nobile and could provide references for the identification of acylated C‐glycosyl flavones in other natural products.